Seasonal variation of particle hygroscopicity and its impact on cloud-condensation nucleus activation in the Beijing urban area - Zhang, Sinan; Shen, Xiaojing; Sun, Junying; Che, Huizheng; Zhang, Yangmei; Liu, Quan; Xia, Can; Hu, Xinyao; Zhong, Junting; Wang, Jialing; Liu, Shuo; Lu, Jiayuan; et al. (Atmospheric environment (1994), 2023)
Hygroscopicity is a key parameter for characterizing the ability of particles to be activated as cloud-condensation nuclei (CCN). In this study, we present a 10-month size-resolved measurement of the hygroscopicity of particles with diameters of 50, 100 and 200 nm in the Beijing urban area using a Hygroscopicity-Tandem Differential Mobility Analyzer (H-TDMA). Compared with that in other studies conducted in China, the hygroscopicity parameter (κ) in this study was relatively higher than that in the Pearl River Delta region but lower than that in the Yangtze River Delta region. As the mass fraction of inorganic matter (especially nitrate) increased, the particles became more hygroscopic during spring and summer, as influenced by the chemical composition. Polluted southerly air masses also enhanced particle hygroscopicity. The CCN concentration was calculated based on κ-Köhler theory, with a moderate supersaturation of 0.4%. The critical diameter of particles as potential CCNs was smaller in spring than that in the other seasons. The critical diameters of aerosols in autumn, winter and spring were 142, 123 and 114 nm, respectively, with calculated CCN concentrations of 1683, 1909 and 1765 cm−3, respectively. Activation ratios, calculated as CCN divided by condensation nuclei (CN), were 0.13, 0.15 and 0.18 in autumn, spring and summer, respectively. During episodes of heavy pollution, the CCN concentration highly depended on the particle mass loading, as the accumulation mode dominated the particle number size distribution and the chemical composition was quasi-homogeneous. However, under other conditions, both particle size and chemical composition were important. This study revealed the relationship between particle hygroscopicity, CCN and air pollution level, and it will be useful for evaluating the environmental and climatic effects of aerosols. •10-month size-resolved particle hygroscopicity was measured in urban Beijing.•Increased mass fraction of nitrate strengthened particle hygroscopicity.•CCN concentration highly depended on particle mass loading under heavy pollution.